The downed runner - Lento, P. H.; Sullivan, W. J. (Physical Medicine & Rehabilitation Clinics of North America, 2005)
Race coverage can be a rewarding experience for the sports medicine clinician. Several conditions are likely to present to the medical tent, and accurate diagnosis is critical to proper treatment. An algorithm approach as outlined in this article can provide a starting point for the assessment of the downed runner. Recognition of the primary causes for collapse can help to instigate the correct treatment approach. A proper history and physical examination often can help to differentiate significant cardiac events from the more innocuous EAC. Furthermore, avoiding immediate i.v. fluids in the downed runner is prudent, at least until an appropriate diagnosis is made. This will help to prevent iatrogenic hyponatremia. In sum, proper preparation and knowledge of the ailments that affect long distance runners will help to maintain an effective medical tent on race day.